Cross-layer multipath routing approach and link quality indicator for QoS provisioning in mobile WMSN - Bharati S. Pochal; Jayashree Agarkhed; Siddarama R. Patil (Institute of Advanced Engineering and Science, 2024)
With the recent advancement in mobile adhoc networks (MANET’s) and technology, applicability, and integration of wireless multimedia sensor networks (WMSN) in MANET’s has led to creation of smart distributed system for high-speed mobile multimedia streaming and real time multimedia traffic transmissions. In this paper, we propose cross-layer multipath routing approach with link quality indicator (CLMRLQI) to compute stable link between two nodes. CLMRLQI discovers stable multipath routes by considering cross-layer routing metrics such as energy and bandwidth to support quality of service (QoS). The simulation scenarios are carried on network simulation tool and QoS parameters such as throughput, PDR, delay, overhead and energy consumption are analysed.